PENGARUH PENERAPAN STRATEGI PEMBELAJARAN THINK TALK WRITE DAN MINAT BELAJAR TERHADAP KEMAMPUAN MENYIMAK TEKS BERITA SISWA KELAS VIII SMP SWASTA FREE METHODIST-1 HELVETIA TAHUN PELAJARAN 2013/2014 - Fromsiska Naibaho (JURNAL TEMATIK, 2015)
This study aims to determine: (1) differences in the ability to listen to the students that learned the news with a strategy Think-Talk-Write and Expository strategies, (2) differences in the ability to listen to the news of students who have a high interest in learning taught by learning strategies Think-Talk -Write higher with students who have a high interest in learning taught by Expository strategy, (3) the ability to listen to news students who have low learning interest taught by learning strategies Think-Talk-Write higher with students who have low learning interest taught by Expository strategy, (4) the interaction between learning strategy and interest in learning to students' ability to listen to the news. The population in this study were all students of class VIII SMP Free Methodist 1 Terrain TP 2013/2014. The sampling technique used is random sampling. These samples included 60 students consisting of 30 students as the group that learned with a learning strategy Think-Talk-Write and 30 students as a group that learned with expository teaching strategy. Instrument research using questionnaires interest in learning and test students' ability to listen to the news. The method used is a quasi-experimental design with 2 x 2 factorial data analysis technique used is a two-lane Anova test at significant level α = 0.05. The results showed that: (1) the ability to listen to students who are taught by learning strategies Think-Talk-Write is higher than students taught by Expository strategy. (Fhitung = 22.9> F table = 1.84), (2) ability to listen to news students who have a high interest in learning taught by learning strategies Think-Talk-Write, higher than students who have a high interest in learning taught by strategy Expository (Fhitung = 3.3> F table = 1.84), (3) Ability to listen to news students who have low learning interest taught by learning strategies Think-Talk-Write, higher than students who have low learning interest taught by Expository strategy. (4) There is interaction between learning strategies and interest in (Fhitung = 0.23 <F table = 1.84).